The meaning of pictures images of personal, social and political identity - Lord, Peter 1948- (Univ. of Wales Press, 2009)
This title features Welsh pictures painted between the 18th and the 20th centuries, and why they matter today. It mainly concerns how pictures are understood by the people who use them - patrons, museum curators, and the general public - rather than by the painters who paint them.